2018
DOI: 10.1589/jpts.30.496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regular Taekwondo exercise on mood changes in children from multicultural families in South Korea: a pilot study

Abstract: [Purpose] The purpose of this study was to investigate the effects of regular Taekwondo training on mood state in children from multicultural families. [Subjects and Methods] Twenty-four children participated in the study. Eight children from non-multicultural families were assigned to the non-multicultural family children group. The remaining 16 children from multicultural families were randomly assigned to the multicultural family children (control, n=8) or multicultural family children trained in Taekwondo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Participation in Taekwondo training can also be effective in emotional and social development, through reducing anxiety, promoting independence and leadership, and controlling aggression [ 36 , 37 ]. In addition, some previous studies have suggested that regular Taekwondo training can be effective in improving mood states, as measured by the POMS test [ 10 , 38 ]. In this study, to verify the effect of Taekwondo training on international students’ mental and social health, a K-POMS-B test and a sociality survey, consisting of three sub-categories of peer relationships, social activity, and perceived discrimination, were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in Taekwondo training can also be effective in emotional and social development, through reducing anxiety, promoting independence and leadership, and controlling aggression [ 36 , 37 ]. In addition, some previous studies have suggested that regular Taekwondo training can be effective in improving mood states, as measured by the POMS test [ 10 , 38 ]. In this study, to verify the effect of Taekwondo training on international students’ mental and social health, a K-POMS-B test and a sociality survey, consisting of three sub-categories of peer relationships, social activity, and perceived discrimination, were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Taekwondo, in particular, has been shown to provide significant psychological benefits to Athletes, such as cognitive and affective self-regulation, improvements in social behavior, and elevated mood (Akehurst, Southcott, & Lambert, 2020;Harwood, Lavidor, & Rassovsky, 2017;Yang, Ko, & Roh, 2018). Taekwondo Athletes have also been observed to have low levels of anxiety, depression, and aggression as well as excellent physical conditions (Bridge, da Silva Santos, Chaabene, Pieter, & Franchini, 2014;Moore, Dudley, & Woodcock, 2019;Quintero et al, 2023;Valdés-Badilla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes generate fatigue after exercise stimulation. In this case, if the fatigue is not eliminated in time, athletes will not be able to adapt to further training load, which will eventually have an adverse effect on the training results [1][2].…”
Section: Introductionmentioning
confidence: 99%